Metoprolol rescues endothelial progenitor cell dysfunction in diabetes - Yan, Lang; Dong, Yi-fan; Qing, Tao-lin; Deng, Ya-ping; Han, Xue; Shi, Wen-jing; Li, Jin-feng; Gao, Fang-yuan; Zhang, Xiao-fang; Tian, Yi-jun; Dai, Xiao-yu; Zhu, Jiang-bo; et al. (PeerJ, 2020)
Added risk portended by diabetes in addition to hypertension has been related to an amplification of endothelial dysfunction. β-blockers are widely used for cardiovascular diseases and improve the endothelial function compared with a placebo. However, the effect of β-blockers on the endothelial progenitor cells (EPCs) function in diabetes is still unknown. Five β-blockers (metoprolol, atenolol, propranolol, bisoprolol, and nebivolol) were tested in EPC functional screening. Metoprolol improved EPC function significantly among the five β-blockers and was chosen for the in vivo tests in STZ induced diabetic mice. Reactive hyperemia peripheral arterial tonometry (RH-PAT) measurements were performed using the Endo-PAT2000 device in diabetic patients. Metoprolol, but not other β-blockers, improved EPC function in both tube formation and migration assay. EPC function was significantly decreased in diabetic mice, and metoprolol treatment restored damaged EPC migration capabilities and circulation EPC number. Metoprolol treatment promoted wound healing and stimulated angiogenesis in diabetic mice. Furthermore, metoprolol significantly enhanced eNOS phosphorylation and decreased O2− levels in EPCs of diabetic mice. In clinical trials, the RH-PAT index was significantly higher in metoprolol-treated versus bisoprolol-treated diabetics. Metoprolol could accelerate wound healing in diabetic mice and improve endothelial function in diabetic subjects, which may be mediated in part by improving impaired EPC function.
Keywords: Endothelial function; Beta-blockers; Endothelial progenitor cells; Angiogenesis; Diabetes